Medical students’ knowledge, attitude, and practice of complementary and alternative medicine: a pre- and post-exposure survey in Majmaah University, Saudi Arabia - Al Mansour,Mohammed; Al-Bedah,Abdullah; AlRukban,Mohammed; Elsubai,Ibrahim; Mohamed,Elsadig; El Olemy,Ahmed; Khalil,Asim; Khalil,Mohamed; Alqaed,Meshari; Almudaiheem,Abdullah; Mahmoud,Waqas; Medani,Khalid; et al. (Advances in Medical Education and Practice, 2015)
Mohammed Abdullah Al Mansour,1 Abdullah MN Al-Bedah,2 Mohammed Othman AlRukban,3 Ibrahim S Elsubai,2 Elsadiq Yousif Mohamed,4 Ahmed Tawfik El Olemy,2 Asim AH Khalil,2 Mohamed KM Khalil,2 Meshari Saleh Alqaed,2 Abdullah Almudaiheem,2 Waqas Sami Mahmoud,4 Khalid Altohami Medani,4 Naseem Akhtar Qureshi2 1College of Medicine, Majmaah University, Al Majma’ah, 2National Center of Complementary and Alternative Medicine, Ministry of Health, 3Department of Family Medicine and Community Medicine, College of Medicine, King Saud University, Riyadh, 4Department of Community Medicine and Public Health, College of Medicine, Majmaah University, Al Majma’ah, Saudi Arabia Background: Evidently, complementary and alternative medicine (CAM) is a recognized medical practice that efficiently uses multiple treatment therapies and techniques in the prevention and management of a variety of human disorders. Many medical schools have integrated CAM curriculum in medical education system worldwide. Research in knowledge, attitude, and practice (KAP) of diverse health professionals exposed to CAM courses is important from many perspectives including improvement in KAP and teaching skills of faculty, together with capacity building and curriculum development.Objective and setting: This pre- and post-design cross-sectional study aimed to assess CAM-KAP of two intakes of medical students in Majmaah University, Saudi Arabia.Methods: The second-year medical students of the first (year 2012–2013) and second (year 2013–2014) intake (n=26 and 39, respectively) were selected for this study. A reliable, 16-item self-administered questionnaire was distributed among all the students for answering before and after the 48-hour CAM course. The data were analyzed using appropriate statistical test of significance.Results: Medical students’ knowledge and attitude toward CAM significantly improved across some subitems of CAM questionnaire with a positive trend in the rest of its items including their views on CAM practices.Conclusion: CAM course tends to ...